Pension Reforms and Adverse Demographics: The Case of the Czech Republic - Martin Stepanek (Charles University in Prague, Institute of Economic Studies (IES), 2017)
Unsustainability of pension systems particularly in developed economies looms large on the horizon due to increasing life expectancy and continuous drop in fertility. In spite of a broad awareness of the issues, there is no consensus on appropriate remedy and little action. In this paper, I present a comprehensive OLG model tailored for simulation of pension reforms and calibrated on real-world data that accounts not only for optimising agents but also for productivity shocks and financial market frictions. The model is used for assessment of alternative pension reforms in the Czech Republic, yet many of the conclusions apply to other countries as well. The estimates show that retirement age will need to increase constantly in the next decades in order to maintain the current levels of replacement rates in the existing PAY-GO scheme and that this result is virtually independent of the level of economic growth. On the other hand, a transition towards a fully funded scheme would be extremely costly and while it would improve system's resistance to demographic changes, it would also substantially redistribute wealth in the society and expose pensions to financial markets risks. The best option overall may then be a well designed multipillar pension scheme, which can provide an optimal balance of performance indicators without leading to excessive costs of transition.
Keywords: H55; H68; I38; J32; 330; pension; OLG; simulation; ageing